Implementasi Multibeam Echosounder sebagai Alat Bantu Pencarian Rambu Penuntun yang Runtuh di Alur Pelayaran Sungai Kapuas Pontianak - Siregar, Nathanael Bagaskara; Danial, Mochammad Meddy; Lestari, Arfena Deah; Meirany, Jasisca; Supriyadi, Asep (Advances In Social Humanities Research, 2024)
The Pontianak Kapuas River has a narrow shipping lane with a one-way route system. To reduce the danger in sailing in the shipping channel, a navigation tool is needed in the form of cardinal buoy. Based on the information obtained, there is a cardinal buoy 1 that has collapsed and endangered the shipping lanes. So it is necessary to carry out a hydrographic-bathymetric survey using the Multibeam Echosounder (MBES) technology. This survey aims to identify the coordinates and direction of the cardinal buoy object. The sounding method is a method used to obtain water depth data in the survey area. After processing the data, it was found that the coordinates of the cardinal buoy that collapsed were 0°4'29" N - 109°10'02" E and experienced a position shift of around ± 38 meters. The cardinal buoy that have been found do not block the shipping lanes because of their position as far as 240.39 meters from the shipping lanes. For this reason, the cardinal buoy that has collapsed does not need to be lifted, only a marker bouy is given,